PENGEMBANGAN E-MODUL MENGGUNAKAN 3D PAGEFLIP PROFESSIONAL PADA MATERI MOMENTUM DAN IMPULS SMA/MA KELAS XI - Fitri, Hammiyati; Maison, Maison; Kurniawan, Dwi Agus (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2019)
This research aims to develop e-modules on the materials of momentum and impulses and know the perception of students. This research is a research and development that uses the Borg and Gall models. The stages of research include potential and problems, data collection, product design, design validation, design revisions, product testing, product and final product revisions. The test subject of this research is XI IPA High school students N 11 Muaro Jambi. The instrument used is a media and material validation poll and a student perception questionnaire. Data is analyzed descriptively. E-modules are developed from the module cover, the map of the position of the module, the learning activities per sub-chapter with examples and exercises and the final formative tests, load materials, videos, animations, simulations. The validation results of media experts and material respectively at 3.68 and 3.1 in good category. The results of the students ' perception analysis obtained an average score overall indicator is 3.45 which is categorized well.